2012
DOI: 10.1055/s-0031-1291609
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided vascular therapy: is it safe and effective?

Abstract: Recent developments in therapeutic endoscopic ultrasound (EUS) have enabled new approaches to the management of refractory gastrointestinal bleeding, including EUS-guided sclerotherapy and vessel embolization. Few cases have been reported in the literature. Eight patients were admitted for severe, refractory gastrointestinal bleeding, seven of whom were actively bleeding. Causes of bleeding were gastric varices secondary to portal hypertension (n = 3); gastroduodenal artery aneurysm or fundal aneurysmal arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 7 publications
1
47
0
1
Order By: Relevance
“…The procedure was successful in both cases treated with epinephrine injection and in two out of four treated with contact thermal coagulation [17]. Gonzalez et al successfully treated a patient who bled from the side branch of gastroduodenal artery with EUS-guided injection of cyanoacrylate, with no recurrence bleeding detected during 14-month followup [18]. …”
Section: Resultsmentioning
confidence: 99%
“…The procedure was successful in both cases treated with epinephrine injection and in two out of four treated with contact thermal coagulation [17]. Gonzalez et al successfully treated a patient who bled from the side branch of gastroduodenal artery with EUS-guided injection of cyanoacrylate, with no recurrence bleeding detected during 14-month followup [18]. …”
Section: Resultsmentioning
confidence: 99%
“…They then used Doppler to confirm the absence of blood flow after therapy and reported a 100% success rate with no re-bleeding at 12 months. Gonzalez et al have reported on the treatment of Dieulafoy lesions, a bleeding pancreatic tumor, a pancreatic pseudoaneurysm, and an intracystic splenic artery pseudoaneursym [30,31]. Thrombin injection via EUS for pancreatic pseudoaneurysm bleeding has also been described [32].…”
Section: Non-variceal Gastrointestinal Bleedingmentioning
confidence: 99%
“…Authors of another study reported the role of EUS in managing gastric lesions like varices, Dieulafoy lesions and arterial malformations [Gonzalez et al 2012]. Sharma and Somasundaram described a patient with a bleeding rectal varix, controlled with the aid of EUS [Sharma and Somasundaram, 2010].…”
Section: Site and Etiology Of Gastrointestinal Bleedmentioning
confidence: 99%
“…Echoendoscope Radial- [Rana et al 2011;Krystallis et al 2012] or linear-array [Kinzel et al 2014;Ribeiro et al 2001;Gonzalez et al 2012;Romero-Castro et al 2007, 2013Lahoti et al 2000;Binmoeller et al 2011;Law et al 2014;Bhat et al 2015] therapeutic echoendoscopes with color Doppler have been used by most endoscopists for localizing and targeting the feeding vessels.…”
Section: Techniquementioning
confidence: 99%